The use of biologics to improve patient-reported outcomes in hip preservation. Issue 1 (17th April 2021) - Sullivan, Spencer W; Aladesuru, Oluwatobi M; Ranawat, Anil S; Nwachukwu, Benedict U
Abstract: Despite lack of clear understanding, the use of biologic treatment methods has increased in the United States. Therapeutic methods, including platelet-rich plasma (PRP), bone marrow aspirate concentrate (BMAC) and hyaluronic acid (HA) among other biologics, are commonly associated with relief of pain in a number of different orthopedic conditions. Within the past two decades, hip preservationists have investigated the roles of these biologic treatments in both non-operative and surgical management of common hip conditions. The purpose is to review the published literature surrounding the application and efficacy of biologics, most notably PRP, BMAC and HA, in the clinical management of hip conditions. The hip conditions examined in this review include hip osteoarthritis, femoroacetabular impingement syndrome and associated labral tear pathology, avascular necrosis of the femoral head and gluteal/hamstring tendinopathy. While our review of the literature suggests that there is support for the implementation of biologics to relieve pain and improve function for hip conditions. Through further research efforts, it is important to stay updated with the clinical efficacy of biologics in hip preservation.